Assessment of Ti-16Nb-xZr alloys produced via PIM for implant applications - GÜLSOY, HAMİT ÖZKAN (SPRINGER, 2018)
Titanium and its alloys are used in production of implants such as knee and hip prostheses due to their superior properties. Ti-Nb-Zr ternary alloys are preferred over other metallic implant materials due to the presence of non-toxic elements, high corrosion resistance, good biocompatibility, and proper mechanical properties. The aim of this work is to investigate the effect of zirconium addition on alpha -> beta phase transformation, microstructure, and mechanical behavior of Ti-16Nb alloy. In doing so, Ti-16Nb-xZr (x: 0, 5, 10, 15 mass%) alloys are produced by powder injection molding, which offers advantages such as low cost, net shape, and easy production of complicated parts for implant fabrication. X-ray diffraction analysis and scanning electron microscope images showed that zirconium behaves as a beta stabilizer and according to differential thermal analysis, and it decreases alpha to beta transition temperature approximately 30 degrees C. It is also revealed that increasing zirconium content caused finer microstructure and hardness of the alloy was raised from 336 HV0.5 to 412 HV0.5 while elastic modulus remains approximately steady between 103 and 110 GPa. It is concluded that Ti-Nb-Zr alloys have been found to be a good alternative to known metallic implant materials.
Keywords: Powder injection molding (MIM); Titanium alloy; Zirconium; Implant materials; TI-NB ALLOYS; MECHANICAL-PROPERTIES; BIOMEDICAL APPLICATIONS; CORROSION BEHAVIOR; ZR CONTENT; POWDER; MICROSTRUCTURE; BIOCOMPATIBILITY; RHEOLOGY